Impact of Mass Media upon Juvenile Delinquency in Basra Central Prison and AL- Maqal Police Station (Medico Legal Update, 2020)
Aim: This study aimed to determine the impact of mass media upon juvenile delinquency in Basra CentralPrison and AL- Maqal Police StationSubjects and Methods: A descriptive analytic study design was carried out at juvenile delinquency in BasraCentral Prison and AL- Maqal Police Station from 3rd February 2019 until 4th April 2019 in AL-Maqal PoliceStation and 14th April 2019 until 14th May 2019 in Basra Central Prison. Non – probability (purposive)sample of 100 juveniles who were Basra Central Prison and AL- Maqal Police Station were selected. Toknow the impact of mass media upon juvenile delinquency using several measures are Content-based MediaExposure Scale (C-ME), International Self-Report Delinquency Questionnaire (ISRD), and Subtypes ofAntisocial Behavior questionnaire (STAB) of 60 items of statements that measure impact mass media onjuvenile’s behavior; and these statements are loaded into seven dimensions including social; psychological;ethical; political; economic; religious; and violent. Reliability of instrument was determined through the useof Alpha Cronbach approach and the instrument validity was determined through a panel of experts. Theanalysis of the data was used descriptive statistics frequencies, percentages, mean, standard deviation andAnalysis of Variance (ANOVA). In order to assess the impact of mass media upon juvenile delinquency.Results: The findings of the present study reveal that indicate to high percentage unsatisfactory behavior(44%) in social and psychological status, (53%) in violent status, while impact upon ethical, political,economic and religious unsatisfactory behaviors have low than third, the total percentage of unsatisfactorybehavior of all sample as (28.3%). Conclusion: The study concluded that the unsatisfactory behavior level of (social, psychological, ethical,political, economic, religious, and violent) dimensions were moderate of juvenile delinquency.